Reducing bias in multivariate analyses due to the modifiable areal unit problem. (2018) - Tuson, Matthew; Kok, Mei Ruu; Yap, Matthew; Vickery, Alistair; Boruff, Bryan; Murray, Kevin; Turlach, Berwin; Whyatt, David
No abstract available